An embodied spirituality: perspectives for a bodily pastoral anthropology - J-A. van den Berg (Acta Theologica)
Important new developments within practical theology and, in particular, within pastoral theology have taken place over the past decades. In terms of a post-foundational practical theology, this article endeavours from a hermeneutical perspective to explore overlaps between various domains of sciences. As part of a re-described spiritual embodied anthropology, it is claimed that the mind-body dualism is outdated and that the roots of human corporeality are to be rediscovered. The article investigates the effect of an emphasis on the biological for a pastoral anthropology in terms of its implications for one’s concept of God, one’s view on personal identity, the affirmation of being relation-orientated, and the importance of context. Taking these perspectives to the marketplace, the article considers the meaning of the spirituality of an embodied soul at work. In formulating these perspectives, the emphasis is on an engagement with the other and his/her world.